Function and expression of class I ribonucleotide reductase small subunit-encoding genes in Mycobacterium tuberculosis and Mycobacterium smegmatis - Mowa, Mohube Betty (My University, 2009)
Ribonucleotide reductases (RNRs) are a class of enzymes catalyzing the de novo reduction of ribonucleotides to deoxyribonucleotides essential for DNA replication and repair. In addition to the class Ib RNR encoding genes, nrdE and nrdF2, Mycobacterium tuberculosis and Mycobacterium smegmatis also contain a homologue of a Chlamydial class Ic small subunit-encoding gene, nrdB. M. tuberculosis also contains an alternate class Ib RNR small (R2) subunit, NrdF1. In M. smegmatis mc2155, the class Ib RNR genes are located on a large chromosomal duplication. M. tuberculosis nrdF2 has been previously demonstrated to be essential for in vitro growth. It was hypothesized that different class I RNR R2 subunits could be used by the tubercle bacilli to survive and persist in the host. To test this hypothesis, function and expression of the class I R2-encoding genes in M. tuberculosis and M. smegmatis was investigated. Arguing against a specialist role for the alternate R2 subunits was the finding that NrdB in both organisms and NrdF1 in M. tuberculosis are individually and collectively dispensable for growth and long-term survival in vitro, resistance to genotoxic stress, adaptation during RNR inhibition by hydroxyurea and virulence in mice. Further confirming the essentiality of NrdF2 in mycobacteria and that NrdB cannot substitute for NrdF2 function in vitro was the finding that nrdF2 is essential for growth of a strain of M. smegmatis mc2155 lacking the duplicated chromosomal region ( DRKIN). DRKIN showed marked hypersensitivity to a wide range of compounds including hydroxyurea and mitomycin C, whereas deletion of only one copy of nrdF2 in M. smegmatis mc2155 resulted in a specific hypersensitivity to hydroxyurea. Through the construction of nrdR-deficient mutants of M. tuberculosis and M. smegmatis, the class Ib RNR genes were shown to be specifically regulated by an NrdR-type repressor, as evidenced by increase in nrdE and nrdF2 transcript levels in nrdR-deficient mutants of M. tuberculosis and M. smegmatis. Interestingly, however, upregulation of these genes did not affect M. smegmatis or M. tuberculosis in vitro growth, DNA damage survival or resistance to hydroxyurea. Together, these observations identify a potential vulnerability in dNTP provision in mycobacteria, and thereby offer a compelling rationale for pursuing the class Ib RNR as a target for drug discovery.